A Tale of Two Towns: A Comparative Study Exploring the Possibilities and Pitfalls of Social Capital among People Seeking Recovery from Substance Misuse. (23rd February 2018) - Weston, Samantha; Honor, Stuart; Best, David
ABSTRACT: Background : Social capital has become an influential concept in debating and understanding the modern world. Within the drug and alcohol sector, the concept of 'recovery capital' has gained traction with researchers suggesting that people who have access to such capital are better placed to overcome their substance use-related problems than those who do not (Cloud and Granfield, 2008), leading to requests for interventions that focus on building social capital networks (Neale & Stevenson, 2015). While accepting that the concept of social capital has enormous potential for addressing the problems associated with drug use, this paper also considers its 'dark side'. Methods : Data were drawn from semi-structured interviews with 180 participants including 135 people who use drugs and 45 people who formerly used drugs. Results : High levels of trust, acquired through the establishment of dense social networks, are required to initiate recovery. However, these 'strong bonds' may also lead to the emergence of what is perceived by others as an exclusive social network that limits membership to those who qualify and abide by the 'rules' of the recovery community, particularly around continuous abstinence. Conclusions : Depending on the nature of the networks and the types of links participants have into them being socially connected can both inhibit and encourage recovery. Therefore, the successful application of social capital within the drugs and alcohol field requires a consideration of not only the presence or absence of social connections but their nature, the value they produce, and the social contexts within which they are developed.